Women’s Agency and Relational Support in Resisting Patriarchy: A Structural Analysis of When Life Gives You Tangerines - Syahla Shofiyah Putri Farizal; Ninuk Sholikhah Akhiroh (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
Patriarchal resistance in popular media is often interpreted primarily as an individual struggle by female characters, leaving the role of interpersonal support within family relationships insufficiently examined. This study analyzes how resistance to patriarchy is represented through Oh Ae-Sun’s actions across her life course and how Yang Gwan-Sik’s support contributes to negotiating patriarchal expectations within the family in the Korean drama When Life Gives You Tangerines. The study employed a descriptive qualitative design using deductive qualitative content analysis of all 16 episodes. The data consisted of scenes, dialogue, actions, nonverbal expressions, and family interactions, which were analyzed through three structures adapted from Sylvia Walby’s theory: household production, culture institutions, and sexuality. The findings show that Ae-Sun’s individual resistance is most explicit in her persistence in maintaining her literary identity, challenging gendered exclusion from leadership, and supporting educational opportunities for her daughter. Her capacity to resist domestic and reproductive expectations is more constrained when patriarchal authority is exercised through the extended family. In these situations, Gwan-Sik’s relational support limits the enforcement of unequal domestic obligations and reproductive demands. The study concludes that private-sphere resistance is represented as a gradual and relational process involving women’s agency, supportive masculinity, negotiation of family authority, and intergenerational changes in gender values.